Health behaviors of Bydgoszcz high school graduates - Kostencka, Alicja; Sławiński, Szymon; Dziembowska, Inga (Journal of Education, Health and Sport, 2016)
Lifestyle affects the physical, mental, social development, health and learning ability. It seems that there are differences in the health behaviors of young females and males, however these differences are not well described. The aim of the current study was to assess the lifestyle of eighteen-years old and to compare their health behaviors of young persons according to their gender. The study was conducted among 98 students of high schools in Bydgoszcz (35 females and 68 males). All participants were 18 years old. The questionnaire was prepared especially for the purposes of the study, a part of the questions of this questionnaire was taken from the Canada Fitness Survey. The physical activity, mode of nutrition, use of stimulants, hours of sleep, time spent in front of screens and the level of stress were taken into consideration while assessing the teenagers’ lifestyle. The lifestyle of high school graduates is worrisome. It is characterized by low level of physical activity, irregular nutrition, not enough fruits, vegetables and water consumed. A large group of young people drink alcohol, smoke tobacco and marijuana, sleep too short. Males also spend too many hours in front of a television, computer or other similar device. Differences in the health behaviors of women and men appear to be significant. The prevalence of alcohol abuse in this group is very high and affects both sexes. The sex differences in the health-promoting behaviors among men and women in this group of adolescents seems to diminish. Observed unhealthy behaviors indicates the urgent need for health education, especially those that educate the student about the value of the person, the value of health, and the development of social skills that underlie personal development. The foremost priority is risk prevention implementation in primary schools. Further research and continuous monitoring of health behaviors in different age groups is needed as well as to implement and permanently evaluate specific, comprehensive programs among children and adolescents.